The plant hunter : a scientist's quest for nature's next medicines - Quave, Cassandra Leah (Viking, 2021)
"A leading medical ethnobotanist tells us the story of her quest to develop new ways to fight illness and disease through the healing powers of plants in this uplifting and adventure-filled memoir. Plants are the basis for an array of lifesaving and health-improving medicines we all now take for granted. Ever taken an aspirin? Thank a willow tree for that. What about life-saving medicines for malaria? Some of those are derived from cinchona and wormwood. In today's world of synthetic pharmaceuticals, scientists and laypeople alike have lost this connection to the natural world. But by ignoring the potential of medicinal plants, we are losing out on the opportunity to discover new life-saving medicines needed in the fight against the greatest medical challenge of this century: the rise of the post-antibiotic era. Antibiotic-resistant microbes plague us all. Each year, 700,000 people die due to these untreatable infections; by 2050, 10 million annual deaths are expected unless we act now. No one understands this better than Dr. Cassandra Quave, whose groundbreaking research as a leading medical ethnobotanist--someone who identifies and studies plants that may be able to treat antimicrobial resistance and other threatening illnesses--is helping to provide clues for the next generation of advanced medicines. In The Plant Hunter, Dr. Quave weaves together science, botany, and memoir to tell us the extraordinary story of her own journey. Traveling by canoe, ATV, mule, airboat, and on foot, she has conducted field research in the flooded forests of the remote Amazon, the murky swamps of southern Florida, the rolling hills of central Italy, isolated mountaintops in Albania and Kosovo, and volcanic isles arising out of the Mediterranean-all in search of natural compounds, long-known to traditional healers, that could help save us all from the looming crisis of untreatable superbugs. And as a person born with multiple congenital defects of her skeletal system, she's done it all with just one leg. Filled with grit, tragedy, triumph, awe, and scientific discovery, her story illuminates how the path forward for medical discovery may be found in nature's oldest remedies"--